A clinico-mycological study of tinea capitis - B Ashvith Shetty; H V Nataraja; Nagarathnamma; M Mallikarjun; S Sacchidanand; B Leelavathi; T N Revathi; G S Asha (Wolters Kluwer Medknow Publications, 2012)
Tinea capitis is the dermatophytosis of the scalp and hair. It is predominant in children especially in the tropical region. The epidemiology and etiology of tinea capitis keeps changing with time and varies considerably with respect to geography and specific population groups. The present study was undertaken to study the incidence, morphological pattern, direct microscopy and to establish the species causing tinea capitis in this geographical area (Bangalore)